Memory and Historical Culture in Early Modern England - Woolf, Daniel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractThe place of memory in the thought and culture of early modern England has been often discussed, but usually in the context of the more esoteric aspects of Renaissance culture, such as "memory theatres." Using printed and manuscript sources, this essay reviews the uses of memory and contemporary attitudes toward its importance, with particular attention to its use in the preservation of the past. A distinction is posited between three levels of memory: personal, community, and social, each of which is studied in turn. It is suggested that the formation of a national historical culture in early modern England derives in part from the changing balance between dependence on memory and the use of the written!printed word to commemorate and communicate the past.